Evolution and Significance of Distance Education: Exploring the Impact and Challenges of Distance Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Distance education has its access to one and all within a very short period of time cutting of allbarriers. Distance education is also essential to attain the cherished goal of the nation for univeralisationof education. Distance education is used to educate people of different ages and to educate courses froma wide range of discipline or areas both vocational and non-vocational. Distance education is essentialfrom the point of view of self-learning and self-improvement of an individual who has been deprived ofreceiving proper education. The varied needs of the students are better fulfilled by distance educationrather than by formal system of education. The desire to improve one’s own qualification andknowledge without disrupting one’s present employment can be made possible by distance education.Distance education leads to self-learning and self-improvement. Here one can learn according to hisown pace. It is a very flexible educational system which is not limited by time and place restriction andsuits to the varied needs of the students of different age groups. Distance education makes highereducation accessible to all sections of society. It is economical in terms of time, energy andmoney.Distance Education can satisfy the educational needs of learners with different social andoccupational backgrounds. It is necessary, however, to verify from time to time whether it has providedthe desired access to the groups for whom it was primarily intended. Moreover, the changing needs andaspirations of anticipated learner groups in particular and society in general can influence the planningand management of distance education system with a view to making the system socially responsive.Therefore, research is needed to identify the needs of distance learners as well as the future targetgroups, keeping in view the general course of socio-economic development of the country. Sincedistance learners belong to a heterogeneous background in terms of age, experience, socio-cultural,educational and occupational backgrounds, sustaining their motivation to continue with courses tillcompletion is a crucial issue. Other factors like personal, occupational, institutional and instructionaldo affect learners’ adjustment with studies in varying degrees. Identification of learners’ environmentalfactors affecting their studies is also an area of research in distance education.